Petrophysical evaluation and volumetric estimation within Central swamp depobelt, Niger Delta, using 3-D seismic and well logs - Y.K. Saadu; C.N. Nwankwo (Egyptian Journal of Petroleum)
Estimation of hydrocarbon volume is a critical issue for the economic aspect of the petroleum industry. It is very key in production to estimate reserves and after considerable production, to determine the efficiency of recovery and also as a basis for advanced studies such as reservoir simulations. The petrophysical parameters and hydrocarbon volume within the Central swamp depobelt in the Niger Delta has been evaluated from seismic and well logs data. Two reservoirs, GA and GB were delineated from the logs. The lithologies are sand and shale sequences. The trapping system were interpreted from seismic sections as anticlinal and fault closures. Two horizons and several faults were mapped from the seismic sections. The faults mapped are mainly synthetic and antithetic, characteristic of the Niger Delta. The seismic to well tie shows a fairly good match. The average porosity and permeability estimated for reservoir GA are 20% and 1338 md respectively. Similarly, the estimated average porosity and permeability for reservoir GB are 21% and 1392 md respectively. The results show that the oil bearing zones in the reservoirs are porous and highly permeable. There was no gas present in either of the reservoirs. The estimated initial hydrocarbon in place for reservoirs GA and GB are 57.84 MMSTB and 48.43 MMSTB respectively. The results of the research shows that the field has a decent hydrocarbon potential and can be economically produced from. Keywords: Reserves, Volumetric, Seismic, Logs, Porosity and permeability